Novel insight into the relationship between organic substrate composition and volatile fatty acids distribution in acidogenic co-fermentation - Huijun Ma; He Liu; Lihui Zhang; Meng Yang; Bo Fu; Hongbo Liu (Biotechnology for Biofuels, 2017)
Abstract Background Co-fermentation is an attractive technology for improving volatile fatty acids (VFAs) production by treatment of solid organic wastes. However, it remains unclear how the composition of different organic matters in solid waste influences the VFAs distribution, microbial community structure, and metabolic pathway during acidogenic co-fermentation. In this study, different organic wastes were added into waste activated sludge (WAS) as co-fermentation substrates to explore the impact of organic matter composition on VFAs pattern and the microbiological mechanism . Results Acetate was the most dominant VFA produced in all fermentation groups, making up 41.3–57.6% of the total VFAs produced during acidogenic co-fermentation under alkaline condition. With the increased addition of potato peel waste, the concentrations of propionate and valerate decreased dramatically, while ethanol and butyrate concentrations increased. The addition of food waste caused gradual decreases of valerate and propionate, but ethanol increased and butyrate was relatively stable. Some inconsistency was observed between hydrolysis efficiency and acidification efficiency. Our results revealed that starch was mainly responsible for butyrate and ethanol formation, while lipids and protein favored the synthesis of valerate and propionate. Microbial community analysis by high-throughput sequencing showed that Firmicutes had the highest relative abundance at phylum level in all fermentation groups. With 75% potato peel waste or 75% food waste addition to WAS, Bacilli (72.2%) and Clostridia (56.2%) were the dominant respective classes. In fermentation using only potato peel waste, the Bacilli content was 64.1%, while the Clostridia content was 53.6% in the food-only waste fermentation. Conclusions Acetate was always the dominant product in acidogenic co-fermentation, regardless of the substrate composition. The addition of carbon-rich substrates significantly enhanced butyrate and ethanol accumulation, while protein-rich substrate substantially benefited propionate and valerate generation. Potato peel waste substantially favored the enrichment of Bacilli, while food waste dramatically increased Clostridia content in the sludge.